Rancangan Bangun Sistem Informasi Pelayanan Pemesanan Dan Pembayaran Untuk Makan Ditempat Berbasis Digital - Rahmat Dedi Gunawan; Widi Astuti (CV. Keranjang Teknologi Media, 2024)
Restaurants engaged in the sale of food and beverages such as geprek chicken, grilled chicken, Oat Chicken, Kremes chicken, pop ice, orange ice, teajuice, cappuccino and othersProblem At lunch and dinner hours customers are quite hemp because the number of employees in this restaurant is only 3 people who serve as waiters, chefs and cashiers and when paying waiters search for matching what menus are ordered verbally this results in The occurrence of crowded customers and will slow down performance because they have to search for orders in advance, the process of making reports is not yet appropriate. Therefore, the solution to the problem in this study will be built an information system that will help consumers order and pay for food when eating on the spot. The development of this system is built using the prototype method and will be implemented with the laravel framework and bootstrap with PHP programming language. The test results that have been carried out using aspects of ISO 25010 web testing, service information systems, ordering and payment get a 100% score on functional suitability testing, which means everything goes as expected. As for usability testing, it scored 91.4% of users from Very Good criteria. This web is run well with all devices both desktop and mobile using the internet.